Laser cladding of PAC 718, tribaloy T-700 and METCO 41 C hard facing powders on AISI SS 304L substrate - More, S. R.; Bhatt, D. V.; Menghani, J.; Paul, C. P.; Desale, G. R. (Materials Science, 2021)
The present investigation aims to deposit the three different hard facing powder (Triboloy T-700 and PAC 718, and TETCO 41 C) on SS 304L using laser cladding technique. The single and overlapped clad track was deposited using 2 kW laser power system. The optimized laser process parameters and 50% overlap clad track was used to deposit a large surface area. The optimum laser process parameters were finalised using single clad structure study. The cross-sections of the clad layers were used to obtain the microstructure and micro-hardness from different regions namely, clad layer, diffusion layer, and substrate. Throughout the study, the laser power was kept constant i.e. 1.2 kW. For single clad deposition, the scanning speed and powder feed rate varied from 0.3 to 0.5 m/min and 4 to 9 g/min, respectively. T-700 and PAC 718 shows uniform developing micro-structure while METCO 41 C shows the development of mixed dendritic and cellular type microstructure. The Triboloy shows the maximum surface hardness of 534 Hv, 321 Hv for PAC 718, and 294 Hv for METCO 41 C.